2022
DOI: 10.1017/s0033291722003415
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy for co-occurring symptoms of depression, anxiety and obsessive-compulsive disorder in children and adults with autism spectrum disorder: a systematic review and meta-analysis

Abstract: Individuals with autism spectrum disorder (ASD) struggle accessing psychotherapy services for comorbidities, including anxiety-, depressive- and obsessive-compulsive disorders (OCD). Apart from cognitive behavioural therapy (CBT) for anxiety in children with ASD, it is unclear whether psychotherapy is effective for these comorbid disorders. We therefore systematically reviewed any form of psychotherapy for co-occurring symptoms of anxiety, depression and OCD in individuals with ASD. Database searches wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Inconsistencies in effect sizes with previous meta-analyses may be attributed to methodological differences such as inclusion criteria (e.g., some included non-adapted generic CBT (Sharma et al, 2021) and non-randomised controlled trials (Perihan et al, 2020; Ung, Selles, Small, & Storch, 2015)) or favouring different measures (Kreslins, Robertson, & Melville, 2015; Sharma et al, 2021; Sukhodolsky et al, 2013) and chosing pooled over separate meta-analyses (Perihan et al, 2020; Ung et al, 2015; Wichers, Van Der Wouw, Brouwer, Lok, & Bockting, 2023). Variation of effect sizes across different raters has been reported elsewhere (Kreslins et al, 2015; Sharma et al, 2021; Sukhodolsky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistencies in effect sizes with previous meta-analyses may be attributed to methodological differences such as inclusion criteria (e.g., some included non-adapted generic CBT (Sharma et al, 2021) and non-randomised controlled trials (Perihan et al, 2020; Ung, Selles, Small, & Storch, 2015)) or favouring different measures (Kreslins, Robertson, & Melville, 2015; Sharma et al, 2021; Sukhodolsky et al, 2013) and chosing pooled over separate meta-analyses (Perihan et al, 2020; Ung et al, 2015; Wichers, Van Der Wouw, Brouwer, Lok, & Bockting, 2023). Variation of effect sizes across different raters has been reported elsewhere (Kreslins et al, 2015; Sharma et al, 2021; Sukhodolsky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of depression and anxiety is common among both adults and children [ 31 ]. In children, the co-occurrence has been associated with a range of health and social problems, which include increased risk of co-occurring conditions, poor use of health care, school problems and high parenting aggravation [ 32 ], which may have long-term impacts. The current study found that the prevalence of co-occurring anxiety and depression was 32.14%, with those with severe symptoms being more than those with mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the ongoing ASD therapy is limited to well-known brain drugs prescribed to both children and adult patients for many ASD co-symptoms: anxiety, depression, hyperactivity, and sleep problems [86,87]. Among these drugs, those effective against attention-deficit/hyperactivity disorders are employed as psychotropic and psychostimulants [1,[86][87][88].…”
Section: Therapiesmentioning
confidence: 99%
“…At present, the ongoing ASD therapy is limited to well-known brain drugs prescribed to both children and adult patients for many ASD co-symptoms: anxiety, depression, hyperactivity, and sleep problems [86,87]. Among these drugs, those effective against attention-deficit/hyperactivity disorders are employed as psychotropic and psychostimulants [1,[86][87][88]. Ongoing research, now intensely investigated, supports an association between ASD and immune/inflammatory mechanisms and proposes the development and future employment for specific inhibitory drugs [89].…”
Section: Therapiesmentioning
confidence: 99%